Political Mediatization in the Mainstream and Digital Era: Jokowi and Dedi Mulyadi - Jailani, Safiruddin; Fatikh, M. Alfin (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study analyses shifts in the mediatisation of digital politics in Indonesia by comparing Joko Widodo (Governor of Jakarta 2012–2014) and Dedi Mulyadi (Governor of West Java 2025–present). Previous research has tended to examine Jokowi and Dedi’s communication strategies in isolation, meaning there is as yet no systematic mapping of the differences between regimes in the media era and the social media platform era that shape patterns of local-national leadership escalation within Strömbäck’s framework of mediatisation. This study aims to fill this gap by examining how the logic of mainstream media and private platforms shapes the symbolic proximity and political visibility of these two figures. Using a descriptive qualitative approach with thematic content analysis of 40 data units (20 news articles from Kompas/Detik/Tempo/Tribun about Jokowi and 20 YouTube/TikTok/Instagram posts by Dedi, selected purposively based on the theme of ‘blusukan’ and visibility indicators), this study maps patterns of mediatisation through a four-phase coding scheme based on Strömbäck, combined with concepts of social media logic. Digital metrics such as conversation volume, views, subscribers, and engagement rates are used descriptively to contextualise patterns of visibility, rather than as tools for statistical testing. Findings indicate that Jokowi’s blusukan are primarily mediated by mainstream media coverage that shapes online political discourse. Conversely, Dedi’s digital blusukan were initially designed as content optimised for platform algorithms. In both cases, the source of political legitimacy has shifted from news intensity and surveys to a combination of visual-emotional narratives and audience engagement on the platform. This study offers the preliminary concept of “platform mastery” to explain how control over the production cycle and content optimisation can shape new forms of communicative power, whilst highlighting the opportunities and limitations of this form of power within the context of digital democracy in developing nations.